2015
DOI: 10.1051/epjconf/20159401051
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study of a bird strike against a windshield

Abstract: Abstract. This paper describes a bird strike study performed at THIOT-INGENIERIE laboratory. For aeronautic requirements, the 220 mm version of the gas gun TITAN is used to perform bird strike on instrumented structures. This paper shows a bird strike on a polycarbonate windshield instrumented with high speed cameras, velocity and force sensors. A crossed work with numerical simulation has been performed to design target support and diagnostic tools. It permits also to demonstrate reliability of the numerical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Three-dimensional loadings are perhaps best used as severe tests of constitutive models developed using much simpler test geometries. In addition bird-strike can be a severe problem for the engines or the pilot cabin wind-shield and is studied by a combination of synthetic and real, albeit dead, birds [163][164][165][166][167][168][169][170][171]. Hypervelocity impact damage to composites is of interest due to their increasing use in spacecraft, satellite bumper shields, and terrestrial armour applications [172][173][174].…”
Section: Ballistic Blast and Shock Loadingmentioning
confidence: 99%
“…Three-dimensional loadings are perhaps best used as severe tests of constitutive models developed using much simpler test geometries. In addition bird-strike can be a severe problem for the engines or the pilot cabin wind-shield and is studied by a combination of synthetic and real, albeit dead, birds [163][164][165][166][167][168][169][170][171]. Hypervelocity impact damage to composites is of interest due to their increasing use in spacecraft, satellite bumper shields, and terrestrial armour applications [172][173][174].…”
Section: Ballistic Blast and Shock Loadingmentioning
confidence: 99%
“…Bird-strike experiments and numerical simulations are of particular interest especially for aerospace engineering applications, where aircraft components must be specifically designed to resist accidental, high-speed soft-body impacts from birds. Experimental studies against different structural components can be found, for example, in [27,28].…”
Section: Bird-strike Effects and Damage Analysismentioning
confidence: 99%
“…However, high costs involved in experiments and complex setups with lengthy preparation time often challenge the development of aircraft structural parts. Moreover, impacted structures during experiments become severely damaged and further reuse is not practicable (Plassard et al, 2015;Heimbs et al, 2018;Orlando et al, 2017).Therefore, commercial computer simulation codes (Abaqus, Ansys, LS-Dyna, MSC Dytran, etc.) are regularly used as alternatives of bird-strike experiments for early-stage research and development of various structural parts, materials, joints, etc.…”
Section: Computational Bird Modelingmentioning
confidence: 99%